Secondary somatosensory and posterior insular cortices: a somatomotor hub for object prehension and manipulation movements - Ishida, Hiroaki; Grandi, Laura Clara; Fornia, Luca (Frontiers in Integrative Neuroscience, 2024)
The secondary somatosensory cortex (SII) and posterior insular cortex (pIC) are recognized for processing touch and movement information during hand manipulation in humans and non-human primates. However, their involvement in three-dimensional (3D) object manipulation remains unclear. To investigate neural activity related to hand manipulation in the SII/pIC, we trained two macaque monkeys to grasp three objects (a cone, a plate, and a ring) and engage in visual fixation on the object. Our results revealed that 19.4% (n = 50/257) of the task-related neurons in SII/pIC were active during hand manipulations, but did not respond to passive somatosensory stimuli. Among these neurons, 44% fired before hand-object contact (reaching to grasping neurons), 30% maintained tonic activity after contact (holding neurons), and 26% showed continuous discharge before and after contact (non-selective neurons). Object grasping-selectivity varied and was weak among these neurons, with only 24% responding to fixation of a 3D object (visuo-motor neurons). Even neurons unresponsive to passive visual stimuli showed responses to set-related activity before the onset of movement (42%, n = 21/50). Our findings suggest that somatomotor integration within SII/pIC is probably integral to all prehension sequences, including reaching, grasping, and object manipulation movements. Moreover, the existence of a set-related activity within SII/pIC may play a role in directing somatomotor attention during object prehension-manipulation in the absence of vision. Overall, SII/pIC may play a role as a somatomotor hub within the lateral grasping network that supports the generation of intentional hand actions based on haptic information.